An optimized 2.4GHz RF power amplifier performance for WLAN system - Mohammed H., Ali; Chakrabarty, C. K.; Abdalla, Ahmed N.; Hock, Goh C. (IOP Publishing Ltd., 2013)
Recently, the design of RF power amplifiers (PAs) for modern wireless systems are faced with a difficult tradeoff for example, cellphone; battery lifetime is largely determined by the power efficiency of the PA and high spectral efficiency which have ability to transmit data at the highest possible rate for a given channel bandwidth. This paper presents the design a multi stage class AB power Amplifier with high power added efficiency (PAE) and acceptable linearity for the WLAN applications. The open-circuited third harmonic control circuit enhances the efficiency of the PA without deteriorating the linearity of class-AB mode of the PA. The voltage and current waveforms are simulated to evaluate the appropriate operation for the modes. The effectiveness of the proposed controller has been verified by comparing proposed method with another methods using simulation study under a variety of conditions. The proposed circuit operation for a WLAN signals delivers a power-added efficiency (PAE) of 37.6% is measured at 31.6-dBm output power while dissipating 34.61 mA from a 1.8V supply. Finally, the proposed PA is show a good and acceptable result for the WLAN system.